Advancing Sustainable Development through SME Engagement: An Empirical Approach - Khan, Muhammad Yar (European Journal of Sustainable Development, 2025)
This study contributes to the business field by operationalizing the components of sustainable marketing and examining their application in SMEs. This study addresses a gap in the literature by conducting a comparative, cross-cultural analysis of sustainable marketing practices in B2B and B2C firms. The focus is on Pakistan, China, and Malaysia, each representing different socio-economic development tiers. Adopting a quantitative research design, data were collected through structured questionnaires from selected organizations in these countries. The findings reveal a consistently positive relationship between sustainable products and sustainable processes. This study also highlights the growing awareness among Pakistani manufacturers regarding sustainable pricing. It also confirms that Chinese consumers are more willing to pay a premium for eco-friendly products. Sustainable distribution practices are emerging in all the three countries, reflecting a shift toward green brands. A key contribution of this study is the development of a conceptual framework based on the 5Ps of the sustainable marketing mix. These findings highlight the growing influence of social and environmental awareness in business strategies and consumer behaviour in Asian markets. This study is offering valuable insights for academia and practice. Keywords: Asia, Malaysia; Pakistan; SMEs; Sustainable Development; Sustainable Product; Sustainable Price; Sustainable Place; Sustainable Personnel; Sustainable Process